2014
DOI: 10.1371/journal.pone.0098667
|View full text |Cite
|
Sign up to set email alerts
|

A Gestational Profile of Placental Exosomes in Maternal Plasma and Their Effects on Endothelial Cell Migration

Abstract: Studies completed to date provide persuasive evidence that placental cell-derived exosomes play a significant role in intercellular communication pathways that potentially contribute to placentation and development of materno-fetal vascular circulation. The aim of this study was to establish the gestational-age release profile and bioactivity of placental cell-derived exosome in maternal plasma. Plasma samples (n = 20 per pregnant group) were obtained from non-pregnant and pregnant women in the first (FT, 6–12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
394
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(417 citation statements)
references
References 38 publications
15
394
2
6
Order By: Relevance
“…These cells are the most abundant cell type of the human placenta and fuse to give rise to the syncytiotrophoblast, which senses and regulates oxygen and nutritional exchange between the mother and fetus during gestation (14,15). Moreover, we established that the plasma concentration of exosomes is greater in normal pregnant women than that observed in nonpregnant women (11). Interestingly, the placenta releases exosomes into maternal circulation at as early as 6 weeks of pregnancy (10).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…These cells are the most abundant cell type of the human placenta and fuse to give rise to the syncytiotrophoblast, which senses and regulates oxygen and nutritional exchange between the mother and fetus during gestation (14,15). Moreover, we established that the plasma concentration of exosomes is greater in normal pregnant women than that observed in nonpregnant women (11). Interestingly, the placenta releases exosomes into maternal circulation at as early as 6 weeks of pregnancy (10).…”
mentioning
confidence: 68%
“…The concentrations of total and placental exosomes in maternal circulation were quantified using a CD63 and placental alkaline phosphatase (PLAP) ELISA as previously described (10,11). PLAP is syncytiotrophoblast-specific marker; therefore, exosomes derived from placental origin are positive for PLAP.…”
Section: Quantification Of Total Exosomes and Pdesmentioning
confidence: 99%
See 1 more Smart Citation
“…(PLAP) is considered as a placental origin marker for exosomes (26), we compared PLAP expression levels in the exosome-containing serum samples and found no significant difference between the sPE and nPTB groups (Fig. 2L).…”
Section: Cd81 Expression Is Up-regulated In the Placentas And Maternamentioning
confidence: 96%
“…In has been suggested that the risk of preeclampsia could associate with an altered relation between various phenotypes of PCDE. The circulating exosomes regulating fetal vascular response play a pivotal role in mobbing progenitor precursors, endothelial dysfunction, cell proliferation, inflammation, vasculogenesis and neoangiogenesis [4,5]. They are key factors contributing in endogenous vascular reparative processes and adaptation to hypoxia / ischemia-induced injury of cytotrophoblast [5].…”
Section: Abstract: Pregnancy; Preeclampsia; Exosomes; Vascular Complimentioning
confidence: 99%